Learning from South Africa's recent summer rainfall droughts: How might we think differently about response?. Issue 3 (18th March 2019) - Archer, Emma R. M.
Abstract : The 2015/2016 and 2016/2017 summer rainfall seasons in South Africa, as well as in the Southern African Development Community region more widely, are generally agreed to be the most severe droughts on record since those of the early 1980s and 1990s. Shortcomings of a more reactive approach to dealing with drought have been well covered in the literature, yet evolution in this regard remains slow. South Africa is currently in the midst of significant change at the local governmental level, as well as likely ongoing change at the national scale. As a result, this provides a potential opportunity to think differently about drought response, taking a longer term and more proactive view, also informed by longer term climate change projections. This commentary provides selected examples of where such an approach might be taken, concluding with hope for an expanded role for scientists in better informing response. Abstract : The recent multi‐year summer rainfall season drought in southern Africa critically impacted key sectors. The event provides us with an opportunity to learn and think strategically about response in these types of events, which are likely to be more frequently experienced in the future.